2021
DOI: 10.1021/acs.est.0c05942
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Comprehensive Toxicity Pathway Model for 17α-Ethinylestradiol in Early Life Stage Fathead Minnows (Pimephales promelas)

Abstract: There is increasing pressure to develop alternative ecotoxicological risk assessment approaches that do not rely on expensive, time-consuming, and ethically questionable live animal testing. This study aimed to develop a comprehensive early life stage toxicity pathway model for the exposure of fish to estrogenic chemicals that is rooted in mechanistic toxicology. Embryo-larval fathead minnows (FHM; Pimephales promelas) were exposed to graded concentrations of 17α-ethinylestradiol (water control, 0.01% DMSO, 4,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 83 publications
1
11
1
Order By: Relevance
“…This observation revealed a varied degree but consistent occurrence of proteinaceous fluid that leaked into the coelom. Similar histological observations have been previously reported in early-life stage fathead minnows (FHM) and Xenopus laevis exposed to the same or greater concentration of EE2, respectively. In fact, Tompsett et al confirmed that this proteinaceous fluid contained Vtg protein.…”
Section: Resultssupporting
confidence: 87%
See 3 more Smart Citations
“…This observation revealed a varied degree but consistent occurrence of proteinaceous fluid that leaked into the coelom. Similar histological observations have been previously reported in early-life stage fathead minnows (FHM) and Xenopus laevis exposed to the same or greater concentration of EE2, respectively. In fact, Tompsett et al confirmed that this proteinaceous fluid contained Vtg protein.…”
Section: Resultssupporting
confidence: 87%
“…On the other hand, fish size and the condition factor at 4 dph and 21 dph were not significantly affected at any of the concentrations tested (Figure S4). These observations were in contrast to previously reported stunted growth in earlylife stage FHM 28 and tilapia. 44 The difference in these observations may be due to species-specific responses, particularly with regard to the length of exposure relative to the life cycle of a given species of fish.…”
Section: Environmentalcontrasting
confidence: 99%
See 2 more Smart Citations
“…Similar 7-day EE2 exposures using pM to low nM concentrations caused significant overexpression of brain AroB and ERα/β transcripts in juvenile Atlantic salmon ( Lyssimachou et al, 2006 ) and 7 dpf zebrafish ( Cano-Nicolau et al, 2016 ; Nasri et al, 2021 ). Specific EE2 effects have also been observed in retina, where a 32-day exposure to low nanomolar concentrations (4–100 ng/L) decreased the outer and inner plexiform layers and total retinal thickness of minnows assessed at 28 days post-hatch ( Alcaraz et al, 2021 ), an effect likely attributed to disrupted and/or heightened estrogen signaling.…”
Section: Introductionmentioning
confidence: 94%